A SYSTEMATIC REVIEW OF SECONDARY PREVENTION STRATEGIES OF CARDIOVASCULAR DISEASE IN LOW- AND MIDDLE-INCOME COUNTRIES - Mr. Peter Johnston, MSc; Prof. Dr. Gerard Leavey (Elsevier, 2023)
Therapeutic Area: CVD Prevention - Primary and Secondary Background: Cardiovascular disease (CVD) is one of the leading causes of mortality globally (1). In recent decades, the disease burden has begun to shift from high income counties (HIC) to low- and middle-income countries (LMICs) as interventions have improved in HICs and diets and lifestyles have altered in LMICs (2). Secondary prevention encompasses identifying and treating those with primary disease, with the goal of preventing further disease progression (3). This systematic review assesses the existing literature on secondary CVD prevention in LMICs, with secondary prevention as the primary focus. In Addition, barriers to broadening the adoption of effective interventions in alternative LMICs are discussed. Methods: This review follows the format outlined in guidelines published by PRISMA (4). Articles which discuss the results and effectiveness of interventions which aimed to reduce secondary CVD progression in LMICs were included. Literature was sourced from the Medline, Cochrane and Embase databases (Figure 1). A variety of standard statistical tests were employed to determine the significance of each studies' relevant CVD outcomes (Table 1). Results: A total of sixteen studies were included in this review, seven of which were found to have a significant effect on secondary CVD outcomes. Pharmacology interventions were the largest grouping comprising eight articles, with five demonstrating significant results. However, three of these five studies compared their respective interventions against placebos, and not existing best standard of care. Four trials examined quality improvement interventions. Two of which, a primary care initiative and an intensive follow up procedure, demonstrated a significant effect. The remaining interventions were not found to be effective in the context of this review (Table 1). Conclusions: This review found that interventions targeting dual antiplatelet therapy, follow up procedures and primary care initiatives were the most effective at improving secondary CVD outcomes. A limitation of this review was the lack of studies from low-income countries, which reduces the applicability of findings to primarily upper middle-income countries.